HUBUNGAN AKTIVITAS FISIK, STATUS GIZI DAN HIPERTENSI PADA PEGAWAI DI WILAYAH KECAMATAN TOMOHON UTARA - Olga Lieke Paruntu; Fred A. Rumagit; Griche S. Kures (Jurnal GIZIDO, 2015)
Hypertension is the most deadly diseases in the world . In Indonesia, the prevalence ofhypertension 25.8 % and 27.1 % in North Sulawesi . This result is lower than themeasurement of blood pressure in Riskesdas survey in 2007 and for the city of Tomohonprevalence of hypertension of 41.6 % . The main causes of hypertension due to less activephysical activity and obesity . The proportion of physical activity are less active North Sulawesihighest obesity 31.7 % and 24.4 % .Research purposes. This study aims to determine the relationship of physical activity,nutritional status and hypertension in employees in the District of North TomohonTypes of research. This is a descriptive observational study with cross sectional studyconducted in July 2014 with a sample of 93 people who were taken with non-probabilitysampling technique with purposive sampling. Nutritional status was determined by BMI(normal 18.5 to 25, 25.1 to 27 obese , overweight > 27 ), physical activity using theInternational Physical Activity ( IPAQ ) , high blood pressure, systolic and diastolic, when≥140/90mmHg. Analysis of the data by using Spearman Rho 's.Research result. The results showed as much as 51.8 % of the subjects engage in moderateactivity ( > 600 METs - min / week ) , 48.4 % had nutritional status of obese and 49 % had anaverage blood pressure of 140 / 90-140 / 105 mmHg Statistical test showed an association ofphysical activity with hypertension, where p = 0.026 ( p < 0.05 ), and their relationship with thenutritional status of hypertension, namely p = 0.008 ( p < 0.05 ) .Conclusion. There is a relationship of physical activity with hypertension in employees in theDistrict of North Tomohon ( p = 0.026 ). Terdapat relationship with hypertension in thenutritional status of employees in the District of North Tomohon ( p = 0.008 ) .